Efficacy and safety of dinutuximab beta combined with GM-CSF and isotretinoin ± chemotherapy as first-line maintenance treatment for pediatric high-risk neuroblastoma in China - Zhao, Wen; Yang, Peiyi; Qin, Jing; Huang, Cheng; Fan, Hongjun; Jin, Mei; Duan, Chao; Wu, Ying; Wang, Xisi; Cui, Chunying; Su, Yan (Frontiers in Oncology, 2026)
BackgroundReal-world evidence on dinutuximab beta for high-risk neuroblastoma (NB) in the Chinese pediatric patients remains limited. This study evaluated clinical efficacy and safety of dinutuximab beta as first-line maintenance therapy in a real-world setting.MethodsWe retrospectively analyzed pediatric patients newly diagnosed with high-risk NB who after induction and consolidation therapy, received dinutuximab beta combined with granulocyte-macrophage colony-stimulating factor and isotretinoin, with or without chemotherapy. The primary outcome was objective response rate (ORR); secondary outcomes included 1- and 2-year event-free survival (EFS) and overall survival (OS) rates, and safety.ResultsTwenty-eight patients were included, with a median age of 56 months (range 27-113) at the initiation of dinutuximab beta. Prior to immunotherapy, 14 patients had achieved complete response (CR) and 14 partial response (PR). Among those with CR, the CR maintenance rate was 78.6% (11/14). In patients with PR, the ORR at the end of treatment (EOT) was 64.3% (9/14). Stratified by treatment modality, PR patients receiving dinutuximab beta with chemotherapy had a higher ORR than those treated with dinutuximab beta alone at EOT [70.0% (7/10) vs. 50.0% (2/4)]. Regarding autologous stem cell transplantation (ASCT) status, all 3 patients who underwent ASCT achieved CR at EOT (ORR: 100%), whereas the ORR among patients without ASCT was 54.5% (6/11). The overall 1-year and 2-year EFS rates were 88.2% [95% confidence interval (CI), 67.4–96.1%)] and 72.4% (95% CI, 41.4–88.8%), respectively; 1-year and 2-year OS rates were both 95.8% (95% CI, 73.9–99.4%). Adverse events (AEs) were common but mostly mild to moderate in severity. Grade 3 or higher AEs occurred predominantly in patients who received combination chemotherapy, including fever, neutropenia, and thrombocytopenia. Pain was effectively managed with most patients requiring only minimal oral morphine (0.01–0.05 mg/kg/d) during cycles 3–5.ConclusionDinutuximab beta shows favorable efficacy for pediatric patients with high-risk NB. Patients treated with prior ASCT or combined with chemotherapy showed trends toward improved response rates and survival outcomes, although optimal treatment regimens required further investigation. AEs are generally manageable, and the use of standardized pain assessment combined with multimodal analgesia has enabled a substantial reduction in morphine exposure.